2021
DOI: 10.1186/s12884-021-04215-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends and factors related to adolescent pregnancies: an incidence trend and conditional inference trees analysis of northern Nicaragua demographic surveillance data

Abstract: Background We aimed to identify the 2001–2013 incidence trend, and characteristics associated with adolescent pregnancies reported by 20–24-year-old women. Methods A retrospective analysis of the Cuatro Santos Northern Nicaragua Health and Demographic Surveillance 2004–2014 data on women aged 15–19 and 20–24. To calculate adolescent birth and pregnancy rates, we used the first live birth at ages 10–14 and 15–19 years reported by women aged 15–19 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
(51 reference statements)
0
1
0
3
Order By: Relevance
“…A baixa escolaridade tem sido fortemente relacionada à gravidez na adolescência, em que muitas adolescentes não frequentam ou desistem da escola em decorrência da gravidez (7,9,(18)(19)(20) . A preocupação em torno disso recai nas consequências futuras que a pouca escolaridade e o baixo nível educacional poderão gerar nas condições socioeconômicas, como menor emprego e renda, bem como limitado acesso à informação e a cuidados de saúde de qualidade, impactando negativamente no crescimento e desenvolvimento infantil.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A baixa escolaridade tem sido fortemente relacionada à gravidez na adolescência, em que muitas adolescentes não frequentam ou desistem da escola em decorrência da gravidez (7,9,(18)(19)(20) . A preocupação em torno disso recai nas consequências futuras que a pouca escolaridade e o baixo nível educacional poderão gerar nas condições socioeconômicas, como menor emprego e renda, bem como limitado acesso à informação e a cuidados de saúde de qualidade, impactando negativamente no crescimento e desenvolvimento infantil.…”
Section: Discussionunclassified
“…Entretanto, é relevante considerar que a ruptura prematura de membranas foi a principal condição clínica apresentada pelas adolescentes, além de gestação prolongada, restrição do crescimento fetal, pré-eclâmpsia, doença hipertensiva específica da gestação, dentre outras. Evidencia--se que gestantes adolescentes estão mais expostas a complicações obstétricas, como ruptura prematura de membranas (11) , pré-eclâmpsia e restrição do crescimento fetal (20) , sendo que estas complicações também podem ser associadas ao parto prematuro (2) . Destaca--se que 15% da amostra foi classificada como "gravidez de risco não especificada", o que deixa uma lacuna e dificulta a compreensão acerca dos reais motivos desta gravidez ter sido considerada de risco.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Several studies in Nicaragua have focused on adolescent pregnancies and childbearing. Studies from the Nicaraguan Demographic and Health Surveys (Pe´rez et al, 2021;Samandari & Speizer, 2010) showed that adolescent pregnancies and live births decreased from 1987 to 2009 but increased thereafter up to 2013. Additionally, adolescent pregnancy was associated with living in low socioeconomic households, especially those with low education.…”
Section: Introductionmentioning
confidence: 99%